Implementasi Budaya 5S (Salam, Senyum, Sapa, Sopan, Santun) Dalam Membentuk Karakter pada Anak Usia Dini - Lulu Alfinah Rodhito; Abi RizqiIllahi (Prodi PIAUD IAI Pangeran Dharma Kusuma Indramayu, 2024)
Early Childhood Education (ECE) is a learning process aimed at children from 0-6 years of age. PAUD aims to support children's physical, emotional, social, and cognitive development through various activities that are appropriate to the stage of development. One aspect of development that needs to be considered in Early Childhood Education (ECE) is the aspect of language development. Because language is commonly used as a means of communication between humans around children. This research uses descriptive qualitative research with the research subjects being teachers and students. The data collection tools that the author uses in this study are observation, interview and documentation. The results of this study are APE with the name Galaxi Box which aims to improve children's language development by playing how the child composes a predetermined word, answering several questions that are in accordance with Educational Aids, and also children are introduced and pronounce letters one by one. The results of the study, the authors concluded that language development in RAM NU Gumawang students in the age range of 5-6 years developed quite well this can be proven by details. of 21 children, 6 children (25%) children (MB) began to develop, 12 children (63%) children BSH (Developing as expected), 3 children (12%) BSB (Developing very well), and (0%) children who have not developed.